Influence of competitive-anxiety on heart rate variability in swimmers - Fortes, L. S.; da Costa, B. D. V.; Paes, P. P.; do Nascimento Junior, J. R. A.; Fiorese, L.; Ferreira, M. E. C. (Journal of Sports Science & Medicine, 2017)
The aim of this study was to analyze the relationship between competitive anxiety and heart rate variability (HRV) in swimming athletes. A total of 66 volunteers (41 male and 27 female) who swam the 400-m freestyle in the Brazilian Swimming Championships participated. Thirty minutes before the 400-m freestyle event, the athletes answered the Competitive Anxiety Inventory (CSAI-2R) questionnaire, then underwent anthropometric (body weight, height, and skinfold thickness) and HRV measurements. Then, at a second meeting, held 3 h after the 400-m freestyle event, the athletes returned to the evaluation room for HRV measurement (Polar® RS800cx, Kempele, Finland). Multiple linear regression was used to evaluate the relationship between competitive anxiety and HRV. The multiple linear regression was performed in three blocks (block 1: cognitive anxiety, block 2: somatic anxiety, and block 3: self-confidence), adopting the forward model. The results indicated a significant association between cognitive anxiety (p = 0.001) and HRV. An increased magnitude of the association was observed when somatic anxiety was inserted in the model (p = 0.001). In contrast, self-confidence showed, which was inserted in block 3, no relationship with HRV (p = 0.27). It was concluded that cognitive and somatic anxieties were associated with the HRV of swimmers. Athletes with a high magnitude of cognitive and/or somatic anxiety demonstrated more significant autonomic nervous system disturbance. Practically, psychological interventions are needed to improve anxiety states that are specific to perform well, and to improve HRV.